An Analysis of Korea’s Investment and Enhancement Capacity for Investment Promotion between Lao PDR and South Korea - SOMSAMONE, Vilayphone; DUANGPASITH, Phatsa; SOUNTHALY, SengAloun (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This research analyzes Korea’s Investment and Enhancement Capacity for Investment Promotion between Lao PDR and South Korea. The purpose of this research is to analyze of Korea’s Investment in Lao PDR in 1988-2018 and to study for a model of investment promotion between Lao PDR and South Korea. The research methodology is based on both primary and secondary data from various sources from theoretical books, related published journals, published government reports, official websites. Regarding the primary data got from observation and interview high-level persons of some related organization in Vientiane capital and LuangPrabang city. The result shows that from 1988 – 1995 Korea has the rank in the top 11 investment share which accounts for 1.75% of total value and then moved up to the top 5 in 1996 – 2000. Base on the research showed that Korea’s investment ranking is changed in every period which Korea’s investment ranking from top 11 moved up to top 3 in Lao PDR during the year 1988 – 2014 and trade value is increased respectively. Moreover, the investments of Korea in Laos are divided into 18 sectors. And those have been invested from 2010 to 2018 by ordering from big to small scales of investment according to the businesses and projects that are being implemented already. The law of investment is divided into 3 types and investments are categorized for 3 types such as 1) Concession enterprises, 2) General enterprises and 3) Enterprises in Special Economic Development Zone (SED) and The Specific Economic Development Zones.